Before and after: A visual glimpse into the coking behaviour of coal macerals. (1st July 2023) - Congo, Tara; Rodrigues, Sandra; Esterle, Joan; Steel, Karen; Maranha, Silvio
Highlights: Coking behaviour of individual macerals was observed using optical microscopy. Greater swelling perpendicular to the bedding layers compared to that parallel. Different pore structures arising from collotelinite and collodetrinite. Visual evidence of semifusinite reactivity. Abstract: Coal petrography as a tool for predicting coke quality has been employed for many decades. This paper first provides a brief review of some of the founding research in this area and secondly proposes and demonstrates a technique for direct optical comparison of a semicoke to its exact piece of precursory coal to observe the pyrolysis behaviour of individual macerals. The technique involves imaging a polished block sample of coal (with the polished face of interest having orientation perpendicular to the bedding layers), pyrolysing the sample in a furnace up to 525°C under conditions attempting to mimic those in a coke oven, embedding the resulting semicoke in resin and lightly re-polishing and re-imaging the surface of interest. Comparison of the optical images of the sample pre- and post-pyrolysis enables a 2-dimensional visual assessment of the coking behaviour of the inherent macerals. This method was applied to two Permian coals: a Mozambican coal with random reflectance of 1.21% and an Australian coal with random reflectance of 1.28%. The main observations were (i) anisotropic swelling, with swelling much greater in the direction perpendicular to the bedding layers compared to that parallel, (ii) noticeably different pore structure arising from the vitrinite macerals collotelinite and collodetrinite, and (iii) visual evidence of semifusinite reactivity. It is intended that application of this technique will enhance the fundamental understanding of maceral specific coking behaviour and thus assist coke-makers with their blend formulations.